Experiences with a high-speed network adaptor a software perspective. - Druschel, Peter
This paper describes our experiences, from a software perspective, with the OSIRIS network adaptor. It first identifies the problems we encountered while programming OSIRIS and optimizing network performance, and outlines how we either addressed them in the software, or had to modify the hardware. It then describes the opportunities provided by OSIRIS that we were able to exploit in the host operating system (OS); opportunities that suggested techniques for making the OS more effective in delivering network data to application programs. The most novel of these techniques, called application device channels, gives application programs running in user space direct access to the adaptor. The paper concludes with the lessons drawn from this work, which we believe will benefit the designers of future network adaptors.
Keywords: Computer systems organization; Computer communication networks; Network architecture and design; Network communications; Computer systems organization; Software; Operating systems; Communications management; Network communication; Performance